Studi Karakteristik Pola Aliran Stratified pada Pipa Horizontal 16 mm - Ilham Dwi Arirohman; Fajar Paundra; Putty Yunesti (Journal of Science, Technology, and Visual Culture, 2021)
The main objective of this research is to find information about the characteristics of air-water stratified flow in a small horizontal pipe. Experimentally, the characteristics of horizontal co-current stratified flow in 16 mm diameter and 10 m long acrylic pipe were investigated by using conductance method and visual method. The study parameter in the form of liquid film thickness measured using a developed parallel wire sensor is supported by visual data taken using a high speed video camera in the fully developed area (180-210D). In order to obtain observations covering all stratified flow subpatterns, a variation of the superficial velocity of water (JL) from 0.01 – 0.1 m/s and the superficial velocity of air (JG) from 4 – 20 m/s were chosen. The observed flow sub-patterns are then mapped in a flow sub-pattern map based on variations in the superficial velocity of air and water, adding the database from previous studies. In addition, it is also known that the average liquid film thickness decreases as JG increases but it increases as JL increases, while the interfacial wave velocity increases with increasing JG and JL.